„Kamienie niepokoją się i stają się agresywne”. Holokaust w świetle ekokrytyki - Ubertowska, Aleksandra (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The article is an attempt to apply the theoretical and analytical tools derived from ecocriticism and the environmental studies, in the analyses of the literature of the Holocaust. The author proposes a thesis that a full recognition of the role of non-human factors (non-humans), such as nature, landscape, climate, plants and animals became only possible after the anthropocentric paradigm in the humanities have been overcome and a new, supra-species kind of “agency”—elaborated from the theory of Brunon Latour—became widespread. The principal part of the essay contains the analyses of the role of landscape, organic and inorganic nature in the autobiographical prose of Piotr Rawicz, Henryk Grynberg and Wilhelm Dichter. In all of the studied writings nature assumes the function of an ethical subject and additionally the role of anti-historical narration.